Selective and sensitive recognition of hexafluorophosphate via an unusual equilibrium between a cationic square host and a PF6- guest - Chun, In Sung; Moon, Sung Jin; Na, Young Mee; Lee, Young-A.; Yoo, Kyung Ho; Jung, Ok-Sang (ELSEVIER SCIENCE BV, 2007)
Hyper-selective and -sensitive recognition of hexafluorophosphate via a rigid molecular square has been carried out in solution. The equilibrium of [Pd(Me(4)en)(Isoni)(PF6)(1/4)](4)(PF6)(3)/[Pd(Me(4)en)(Isoni)](4)(PF6)(4) (Me(4)en = N,N,N',N'-tetramethylethylenediamine- Isoni = isonicotinate) has been monitored via a suitable combination of electrostatic interactions and size effects between a cationic square host and a PF6- guest. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: ANION RECEPTOR; NO3; CF3SO3; METAL